Pfeiffer library : CD-ROM, Version 4.0 : a comprehensive resource of more than 2500 exercises, assessments and games for trainers. (New Jersey : John Wiley, 2008)
The Pfeiffer library represents the single, most comprehensive set of experientially-based resource materials available to human resource facilitators, trainers, and consultants. The library offers a wealth of stimulating ideas and a varied source of practical, read-to-use materials than can be freely customised and reproduced for training purposes.
Απαιτήσεις συστήματος για Windows : IBM-compatible PC with Pentium or higher processor, Windows 2000, XP, Vista, 350 megabytes of hard disk space for the full installation, 25 megabytes for the compact installation, CD-ROM drive, is not for use on a Mac.
Keywords: Human capital -- Management -- Handbooks, manuals, etc; Human services personnel -- Training of -- Handbooks, manuals, etc; Personnel management -- Handbooks, manuals, etc